Inspiration or risk? How social media marketing of plant-based meat affects young people’s purchase intention - Li, Tingting; Wang, Desheng; Yang, Zhihao (Frontiers in Psychology, 2022)
As an alternative protein product to animal meat, plant-based meat is considered to play an essential role in improving animal welfare and protecting the environment. However, why do a few consumers choose plant-based meat but others do not? Despite the increasing research on plant-based meat marketing, little is known about the psychological mechanism by which plant-based meat marketing affects consumers’ purchasing decisions. We utilize the cognitive information processing framework and integrate it with dual-system theory to understand how social media marketing of plant-based meat influences cognitive fluency, customer inspiration, perceived risk, and purchase intention. Three studies (i.e., Studies 1, 2, and 3) show that social media marketing can increase consumers’ purchase intention of plant-based meat more than traditional marketing. In Study 1, increased intensity of social media marketing can enhance consumers’ cognitive fluency and further promote purchase intention. Study 2 explores how cognitive fluency relates to purchase intention through two different psychological mechanisms. We suggest that a higher level of cognitive fluency increases customer inspiration and improves purchase intention. However, a lower level of cognitive fluency reduces purchase intention by increasing perceived risk. Study 3 manipulated members’ status of in-group or out-group to show a boundary condition for the effect of brand community identity on purchase intention. These studies provide insight into how brand marketers can use social media to promote consumer inspiration and advertising engagement, how managers can offer fluency‐increasing mechanisms to ensure a low level of perceived risk, and how enterprise practitioners may want to consider brand community publicity to attract out-group members.